Boosting EFL learners’ commitment and enjoyment in language learning through social networking: A literature review - Li, Bing (Frontiers in psychology, 2022)
Social networking applications have been designed as innovative technologies used by the higher education section to enhance the acquisition of literacy skills, driving learners to engage in online learning platforms. Such tools such as social networking have also been proven to facilitate teaching and learning; therefore, educational programs and universities are increasingly making use of networking sites to form connections with students and to offer online instructional content. This trend has placed questions, regarding the effect of social media on language learning and its potential use as an effective instructional tool. The constructive role of enjoyment did not obtain equal academic consideration in the EFL learning milieu until Positive Psychology was presented to L2 education. Using social networking, users find online tasks appealing and experience the enjoyment that, in turn, impacts their behavioral intention to use them positively. Commitment is another factor that refers to the degree to which students are involved in learning enthusiastically. This construct concerns the extent to which students are loyal to learning, textbooks, and class etiquette. As it contributes to the quality of learning, it is considered a prerequisite for students’ academic success and educational attainment. Based on the role of the above-mentioned constructs in language learning, the present review tries to consider the role of social networking in boosting EFL students’ commitment and enjoyment. Consequently, some implications are presented for academic stakeholders in the quest of considering the role of social networking in language education.